p-Value Cummulative Sum (CUSUM) Chart: A Tool for Monitoring InflationRate - Braimah, O.J.; Jaiyeola, S.B.; Edokpa, I.W.; Rabiu, M. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2016)
This study is aimed at analyzing the rates of Inflation and designing p-Value Cumulative Sum (CUSUM) chart. The dataused in this study is a secondary data on Inflation rates in Nigeria (January, 2002 to December, 2011) obtained from theLibrary of Central Bank of Nigeria (CBN), Ilorin, Kwara State. Analysis on the Inflation rates in Nigeria recorded duringthe years of study (2002-2011) was carried out using Cumulative Sum (CUSUM) and p-value Cumulative Sum (pCUSUM) control chart schemes. A current statistical software (R) was used to analyze and plot the charts in this study.The result obtained from the analysis revealed that the p-value CUSUM detected a shift at sample number 65, while theordinary CUSUM chart defected at point 67. This makes the p-CUSUM control chart a better statistical tool in detectingsmall shift in the process level than ordinary CUSUM control chart scheme